Вплив різноманітних методів навчання на успішність студентів 1 та 2 курсів при вивченнш анатомії людини в ЗДМУ - Вовченко, Михайло Борисович; Vovchenko, M. B. (My University, 2014)
У роботі наведено дані щодо покращення успішності студентів у вищій школі, яка пов’язана з підвищенням ефективності професійної підготовки студентів завдяки використанню різноманітних методів навчання на кафедрі анатомії людини, оперативної хірургії та топографічної анатомії в ЗДМУ. The paper presents the data on improving academic performance of students in the higher school, which is associated with the increase of the effectiveness of professional training of students through the use of various teaching methods at the Department of Human Anatomy, Operative Surgery and Topographic Anatomy of ZSMU.
Influence of different teaching methods on progress of 1st and 2nd year students in the study of human anatomy in ZSMU